2018
DOI: 10.5194/bg-15-2835-2018
|View full text |Cite
|
Sign up to set email alerts
|

A model based on Rock-Eval thermal analysis to quantify the size of the centennially persistent organic carbon pool in temperate soils

Abstract: Abstract. Changes in global soil carbon stocks have considerable potential to influence the course of future climate change. However, a portion of soil organic carbon (SOC) has a very long residence time (> 100 years) and may not contribute significantly to terrestrial greenhouse gas emissions during the next century. The size of this persistent SOC reservoir is presumed to be large. Consequently, it is a key parameter required for the initialization of SOC dynamics in ecosystem and Earth system models, but th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 57 publications
1
28
0
Order By: Relevance
“…While research suggests that more complex organic molecules have higher thermal stability (Lopez-Capel et al, 2005;Yang et al, 2006), contradictory results have also been reported (Rovira et al, 2008). Several studies have also found good correlations between thermal stability indices and biological stability (Peltre et al, 2013;Soucémarianadin et al, 2018) and model-derived stable C pools (Cécillon et al, 2018). However, other studies have found that new carbon preferentially flowed into more thermally stable fractions (Helfrich et al, 2010;Schiedung et al, 2017), suggesting that the relationship between thermal stability and SOM cycling concepts may not be straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…While research suggests that more complex organic molecules have higher thermal stability (Lopez-Capel et al, 2005;Yang et al, 2006), contradictory results have also been reported (Rovira et al, 2008). Several studies have also found good correlations between thermal stability indices and biological stability (Peltre et al, 2013;Soucémarianadin et al, 2018) and model-derived stable C pools (Cécillon et al, 2018). However, other studies have found that new carbon preferentially flowed into more thermally stable fractions (Helfrich et al, 2010;Schiedung et al, 2017), suggesting that the relationship between thermal stability and SOM cycling concepts may not be straightforward.…”
Section: Introductionmentioning
confidence: 99%
“…However, our comparison shows that models with similar structure come to similar conclusions for SOM turnover. For example, the one-pool model in Clifford et al (2014) was quite similar in turnover rates to that in Luo et al (2016) but does not match well with two-pool models. Then again, the rates for the two-pool models of this study, and the studies by Ahrens et al (2014) and Hararuk et al (2017), were very similar in their minima and maxima, for both the slow and fast SOM pools, which shows that only models with a similar number of pools and transformations could be compared.…”
Section: Modelmentioning
confidence: 71%
“…The predictions of mechanistic models usually fail to account for the three main statistical uncertainties in (1) inputs, (2) scientific judgments resulting in different model setups and (3) driving data (Wattenbach et al, 2006). However, with a Bayesian calibration framework such as that implemented in UCODE 2014, almost any model can be made probabilistic, so uncertainties in parameters and outputs can be assessed, even for projections into the future (Clifford et al, 2014). As this study focused on Bayesian calibration and we used an established model, we mainly address parameter uncertainty, although input uncertainty was also included through the weighting process.…”
Section: Parameter Uncertainty As Estimated With Bayesian Calibrationmentioning
confidence: 99%
See 2 more Smart Citations